2002
DOI: 10.1148/radiol.2232010221
|View full text |Cite
|
Sign up to set email alerts
|

Are Gadolinium-based Contrast Media Really Safer than Iodinated Media for Digital Subtraction Angiography in Patients with Azotemia?

Abstract: Are gadolinium-based contrast media really safer than iodinated media for digital subtraction angiography in patients with azotemia?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 31 publications
1
79
0
2
Order By: Relevance
“…In an ischemic rat model it was found that intra-aortic injections of gadopentetate and diatrizoate, both with an osmolality of about 2.0 osmol/kg water, caused a similar decrease in GFR measured as creatinine clearance. However, the dose of iodine atoms appeared to have been 10 times higher than that needed to achieve the same attenuation as the Gd-CM during an XRA study at 80 kV (21). Thus if equal-attenuating doses had been used it seems reasonable to assume that the nephrotoxic effect of diatrizoate had been much less.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In an ischemic rat model it was found that intra-aortic injections of gadopentetate and diatrizoate, both with an osmolality of about 2.0 osmol/kg water, caused a similar decrease in GFR measured as creatinine clearance. However, the dose of iodine atoms appeared to have been 10 times higher than that needed to achieve the same attenuation as the Gd-CM during an XRA study at 80 kV (21). Thus if equal-attenuating doses had been used it seems reasonable to assume that the nephrotoxic effect of diatrizoate had been much less.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration at which I-CM are equal-attenuating with 0.5 M Gd-CM may vary with the x-ray tube kilovoltage (kV) used (30), which, in turn, may depend on patient size. We therefore used a concentration of a commonly used nonionic monomeric I-CM causing roughly the same attenuation of x-rays as an 0.5 M Gd-CM at the commonly used 70 -90 kV for XRA (ie, 0.18 M solution of iohexol [70 mg I/mL]) (21). We also used an 0.5 M iohexol solution (190 mg I/mL), which contains the same number of CM molecules as 0.5M Gd- CM, but three times the number of attenuating atoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no human studies comparing their nephrotoxic effects at volumes and concentrations resulting in the same x-ray attenuation [9,10]. The substitution of Gd-for I-CM appears contradictory not least in renal angiography/angioplasty procedures [1, 4,11], since osmotoxicity is an important factor in the pathophysiology of contrast medium induced nephropathy (CIN) [12,13] and direct injections of high-osmolal solutions, including CM, into the renal artery may be deleterious to the kidney [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%